Blind Spots in African Management Education: An Examination of Issues Deserving Greater Attention. (3rd April 2018) - Lee, Michelle P.; Thomas, Howard; Thomas, Lynne; Wilson, Alexander
Abstract : There is reason to be optimistic about management education in Africa given the growth in the number of business schools on the continent and continued efforts at raising quality. There remains room for improvement in the field, of course, and the issues and challenges that need to be tackled have been written about elsewhere (e.g. African Management Initiative (AMI), 2013; AMBA, 2015; Thomas et al., 2016). The study reported here has the more nuanced purpose of understanding the blind spots that persist in the field. These are issues that are largely ignored or receive insufficient attention because their significance is underestimated. Through a series of structured in-depth interviews with leading management educators and stakeholders, we uncover three potential blind spots to do with a lack of demand-side orientation, unequal access to management education, and the need for glocalization.